2021
DOI: 10.1111/nph.17682
|View full text |Cite
|
Sign up to set email alerts
|

How will global change affect plant reproduction? A framework for mast seeding trends

Abstract: Summary Forest ecology traditionally focuses on plant growth and survival, leaving seed production as a major demographic process lacking a framework for how it will be affected by global change. Understanding plant reproductive responses to changing climate is complicated by masting, the annually variable seed production synchronized within populations. Predicting trends in masting is crucial, because masting impacts seed predation and pollination enough to override simple trends in mean seed production. Prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 45 publications
4
43
0
Order By: Relevance
“…Therefore, a better understanding of mineral nutrient tree demand, absorption capacity and allocation during reproduction cycles will help design species-specific fertilization treatments, with the ultimate goal of shortening reproduction cycles and increasing gross seed production in the long term. In line with this, previous studies in different species have suggested that N-or P-fertilization enhances tree growth (Turner et al, 2002;Jasim, 2013), improves pollen, ovule viability and seed production (Callahan et al, 2008;Smaill et al, 2011;Ghanem et al, 2014;Bogdziewicz et al, 2017), and reduces the interval of masting events (Bogdziewicz, 2022).…”
Section: Introductionsupporting
confidence: 60%
“…Therefore, a better understanding of mineral nutrient tree demand, absorption capacity and allocation during reproduction cycles will help design species-specific fertilization treatments, with the ultimate goal of shortening reproduction cycles and increasing gross seed production in the long term. In line with this, previous studies in different species have suggested that N-or P-fertilization enhances tree growth (Turner et al, 2002;Jasim, 2013), improves pollen, ovule viability and seed production (Callahan et al, 2008;Smaill et al, 2011;Ghanem et al, 2014;Bogdziewicz et al, 2017), and reduces the interval of masting events (Bogdziewicz, 2022).…”
Section: Introductionsupporting
confidence: 60%
“…However, during deployment, only a minority of Q. robur trees—both those containing traps and those across each site—appeared to have live catkins that contained fresh pollen. The remaining Q. robur trees contained seemingly moribund catkins, often with stunted growth, possibly as a consequence of an unusually cold and wet May (Met Office, 2021), although pollen production may have also been low in response to a probable mast event the previous year (Bogdziewicz, 2021; Whittle, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…There is a concern that lowered interannual variability and synchrony of masting might weaken the satiation effect and consequently lower plant recruitment ( 11 , 47 , 51 ) (see refs. 52 , 53 for potential mechanisms of such change). In English populations of European beech ( Fagus sylvatica ), global warming resulted in less synchronized and more even seed production, which in turn increased losses to seed predators ( 47 ).…”
mentioning
confidence: 99%